Age dependence of flow velocities in basal cerebral arteries. Issue 6 (June 1988) - Bode, H; Wais, U
Abstract : Flow velocities in the basal cerebral arteries were studied by transcranial Doppler sonography. A longitudinal study was undertaken on 25 healthy newborn babies during the first 20 days of life, and a cross sectional study was performed on 112 healthy children between 1 day and 18 years of age. A rapid linear increase of flow velocities was found within the first 20 days with higher velocities in neonates of higher birth weight and gestational age. Maximal values were recorded at the age of 5 to 6 years. After that the velocities decreased linearly to 70% of their maximum at the age of 18 years. Reference values were derived from the data considering age and birth weight. The increasing flow velocities probably reflect the increasing cerebral blood flow during the first years of life. Our results also support the hypothesis of a decrease in cerebrovascular resistance during infancy. With the technique of transcranial Doppler sonography and the introduced reference values normal and abnormal intracranial flow velocities can now be assessed by non-invasive methods in all paediatric age groups.